Faulty Sensor Detection Mechanism in Smart Hydroponic System - Deiwien, Kairen; Jamil, Ansar (Evolution in Electrical and Electronic Engineering, 2022)
Smart hydroponic is a method to cultivate various kinds of a plant using water as a medium to grow the plant. Smart hydroponic using sensors such as Total Dissolve Solids (TDS) sensors, temperature sensors, ultrasonic sensors, etc. However, the rapid degradation over a long period of use caused the TDS sensor to provide inaccurate readings and lead to malfunction in the system. Therefore, in this paper, the author designed a faulty sensor detection mechanism in a smart hydroponic system specifically for TDS sensors. Arduino Uno Board and TDS sensor is the main component used in this paper. A reference value was taken and used as the main comparison to the second reading of the TDS Sensor. In this paper, the faulty sensor detection mechanism in the smart hydroponic system successfully functions. For future use, this faulty sensor detection mechanism can be applied to the other sensor used in the smart hydroponic system.